Тheoretical foundations of exhibition activity research - Iryna Panova; Mykola Pysarevskiy; Danylo Semenenko (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2024)
Exhibition activity is an important element of the modern cultural and economic sphere, which is reflected in various formats and concepts. The essence of this phenomenon is to create a platform for public display of products, ideas, creativity and achievements in various fields of life. Exhibitions bring together both producers and consumers, creating a unique opportunity to share experiences, ideas and contacts. Ukraine, like many other countries, has its own organizational and legal framework for state regulation of exhibition activities. This framework includes legislative acts that define the procedure for organizing and holding exhibitions, establish rules of participation for organizers and exhibitors, and determine liability for violation of the established norms. Foreign experience in implementing exhibition projects can be an important source of learning and innovation for Ukraine. Many countries are actively using exhibitions as a tool to promote economic and cultural development, introducing new technologies, stimulating tourism, and maintaining international relations. The object of research is exhibition activity. The subject of research is exhibition activity theoretical foundations of exhibition activity research. The goal of the study is to investigate the scientific and theoretical substantiation of exhibition activity as a factor in tourism development. The tasks set to achieve the goal are to study the essence and definition of “exhibition activity”; to consider the organizational and legal framework for state regulation of exhibition activity in Ukraine; to study foreign experience in implementing exhibition projects. To achieve this goal, the following research methods were used: analytical, evaluative, comparative, statistical, graphical, descriptive, and cartographic. Conclusions: it is found that exhibition activity is an important mechanism for promoting the development of economy, culture and international cooperation. It is highlighted that knowledge of the essence of this phenomenon, understanding of the organizational and legal framework in the country and analysis of foreign experience help to improve and develop the exhibition sphere in the country.